Do Oil-Rich GCC Countries Finance US Current Account Deficit? - Shawkat Hammoudeh; Ramazan Sari; Eisa Alesia (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Given the secrecy that wraps the flows of the GCC countries' petrodollar surpluses to the United States and the pressures on these countries to spend and recycle more, this study attempts to uncover the direct and reverse causal relationships between the GCC financial accounts and the US current account deficit. It examines whether the GCC petrodollar surpluses are a global savings glut (an external factor) that causes the US current account deficit or in contrary this deficit is home-grown and the petrodollar savings glut hypothesis does not hold. It particularly focuses on world's largest oil exporter to find out if the homegrown deficit hypothesis for the world's largest oil consumer holds. It also investigates which types of investments or components of GCC financial accounts help cause the US deficit the most. The implications and policy recommendations for this growing source of global external imbalances are also provided.
Keywords: F21; 330; Capital account; Financial account; Direct and reverse causality